Role of notch signal in angiotensin II induced pulmonary vascular remodeling - Qiao, Li-Na; Xu, Hong-Bo; Shi, Kun; Zhou, Tong-Fu; Hua, Yi-Min; Liu, Han-Min (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2013)
Objective: Notch signal is particularly important to vascular remodeling during the process of embryonic development, vessel repair and tumor growth, but there are few studies about pulmonary vascular remodeling in pulmonary hypertension. This study was to explore the effect of inhibiting Notch signal on pulmonary vascular remodeling induced by angiotensin II. Methods: Vessel strips taken from healthy Wistar rats were cocultured with extrogenous angiotensin II and the potent smooth muscle cell proliferation stimulators for 7 days. Vascular wall thickness, proliferating cell nuclear antigen (PCNA) positive cell rate, and caspase-3 positive cell rate were examined in vessel strips. Some of the vessel strips were cultured with angiotensin II and γ-secretase inhibitor DAPT, a Notch signaling inhibitor, for 7 days. The levels of Notch 1 to 4 receptor and HERP1/2 mRNA were ascertained by FQ-PCR. Results: Angiotensin II stimulation in the cultured normal pulmonary arteries resulted in an increase in the vascular medial thickness by nearly 50%, and a significant increase in the PCNA positive cell rate and a decrease in the caspase-3 positive cell rate (P